Knowledge and Attitude of Women Regarding Mammogram and Other Screening Modalities for Breast Cancer in a Selected Hospital, Kottayam - Sr. Ligi Poonel; Sheba Elsan Mathew; Aparna Thomas; Archana J.; Archana Subash; Ardra Muralidharan; Arunthathi Mohanan; Ashly P. Lukose; Assumpta Ann Shaiju; Shihana Ismail; Vrindamol C.V. (International Journal of Oncological Nursing and Practices, 2023)
The present study was conducted at Caritas Hospital, to assess the knowledge and attitude of women (30–50 years) regarding mammogram and other screening modalities. The study aimed to evaluate women's understanding of mammograms and various breast cancer screening methods, gauge their attitudes toward mammograms and other screening options, investigate the relationship between women's knowledge and attitudes regarding these screening methods, explore any associations between knowledge and certain demographic factors, and examine any associations between attitudes and specific demographic variables. The research followed a non-experimental descriptive design and employed random sampling to select a sample of 50 participants from the population. A structured questionnaire was utilized to assess knowledge, while a five-point Likert scale was employed to measure attitudes. A pilot study was conducted to assess the study's feasibility, and data collection took place between September 16, 2022, and September 17, 2022. The data analysis comprised both descriptive and inferential statistical methods. The findings of the study reveal that among 50 samples, majority (62%) of the sample had good knowledge, 22% had average knowledge, 12% had excellent knowledge and only 4% had poor knowledge regarding mammogram and other screening modalities, 28 (56%) samples had favourable attitude, 22 (44%) had neutral attitude and none of them had unfavourable attitude. A statistically insignificant correlation exists between women's knowledge and their attitudes towards mammograms and other screening methods, as indicated by the 'r' value of 0.124, which is lower than the critical table value of 1.677 at a significance level of 0.05. There is no significant association found between the knowledge score of women regarding mammogram and other screening modalities and selected demographic variables such as age, occupation, number of breast-fed children and area of living. There is no significant association between the attitude score of women regarding mammogram and other screening modalities and selected demographic variables such as age, occupation, number of breast-fed children and area of living. The study's results have relevance for nursing practice, nursing education, and nursing research. Early detection is crucial in the management and control of breast cancer, given that it is the most prevalent cancer among women.
Keywords: Knowledge; attitude; mammogram; screening modalities